Pengaruh Pajak Dan Tunneling Incentive Terhadap Trasnfer Pricing - Putri Gantine Lestari (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
The Economic globalization had a huge impact on the development of international transactions. It is not uncommon for many companies to expand their business to foreign countries by forming multinational companies in several countries by making various investments and transactions on an international scale, one of which is by conducting transfer pricing. This study aims to see the effect of taxes and tunneling incentive on transfer pricing. This research method is quantitative research using multiple regression. The sample of this research is all multinational manufacturing companies listed on the Indonesia Stock Exchange 2017-2019 period, there 16 companies so that the total sample obtained is 48 samples. Based on the results of the research, it was found that taxation partially affected to transfer pricing and tunneling incentives had no effect on transfer pricing while simultaneously taxes and tunneling incentives had an effect on transfer pricing.